TCP/IP embedded internet applications. - Insam, Edward, ....- (Amsterdam : Newnes, 2003)
Samenvatting:Introducing the technology from square one through real-world designapplications, this book will significantly reduce R&D time - and spend.Eddie Insam's approach to the internet protocols TCP/IP is to exploretheir potential as a practical tool for design engineers building webcommunication and capabilities into embedded systems for the nextgeneration of electronic products.Eddie Insam introduces the range of possibilities open tointernet-enabled designs, including automated fault and low-stocknotification, remote environmental control, control of test andmeasurement equipment, and programming responses based on data collectedlocally. These techniques are introduced as they key to a new level ofinteractivity between customer and manufacturer or service provider aswell as a the means for users to communicate with electronic devices inincreasingly useful and user-friendly ways. These new opportunities areintroduced with the level of practical detail required for electronicdesigners getting to grips with turning the next phase of the internetrevolution into reality.The scope of this book encompasses electronic design, networkingapplications and wireless applications using Bluetooth and 802.11 (WiFi).The case studies are not based on one specific device, but listings areprovided where required.
Keywords: Computernetwerken; Protocollen